Effects of a novel non-pharmacological intervention based on respiratory biofeedback, neurofeedback and median nerve stimulation to treat children with ADHD - Santamaría-Vázquez, Eduardo; Estudillo-Guerra, Anayali; Ali, Lna; Martinez, Diana; Hornero, Roberto; Morales-Quezada, Leon (Frontiers in Human Neuroscience, 2025)
IntroductionAttention deficit hyperactivity disorder (ADHD) is a neurodevelopmental condition that affects cognitive, academic, behavioral, emotional, and social functioning, primarily in children. Despite its high prevalence, current pharmacological treatments are not effective in 30% of cases and show poor long-term adherence. Non-pharmacological interventions can complement medication-based treatments to improve results. Among these therapies, neurofeedback (NFB) and respiratory biofeedback (R-BFB) have shown promise in treating ADHD symptoms. Moreover, median nerve stimulation (MNS) can help to enhance the efficacy of these treatments, but it has never been explored in this context. This study aimed to: (1) investigate the effectiveness of a combined R-BFB and NFB intervention to treat ADHD, and (2) explore the potential benefits of MNS in enhancing the proposed intervention.MethodsSixty children with ADHD participated in the study, divided into two experimental groups. The active group received verum MNS, and the sham group received sham MNS. Both groups performed the NFB/R-BFB treatment. Clinical assessments (i.e., Conner's parent rating scale) and electroencephalography (EEG) measurements were taken before the intervention, immediately after treatment, and one month later.ResultsThe results showed that the combined therapy significantly improved behavioral problems, anxiety, hyperactivity, and impulsivity-hyperactivity. Moreover, MNS enhanced the positive effects of the intervention, as the active group achieved higher improvement compared to the sham group. EEG analysis revealed significant changes in spontaneous brain activity, with an increase in frontal theta power (p = 0.0125) associated with reduced anxiety, which might explain the clinical outcomes. These changes were maintained 1 month after the intervention (p = 0.0325). Correlations between EEG changes and clinical outcomes were observed, suggesting a potential relationship between neurophysiological markers and ADHD symptoms measured by standardized scales.DiscussionThe study findings suggest that the proposed R-BFB/NFB intervention may be an effective non-pharmacological therapy for ADHD, with the additional application of MNS potentially enhancing its effects.